Automation of Remote Laboratory Device Configuration File Management - Liandaru, Putu Gde Qwat Bayu; Indriyanta, Gani; Purwadi, Joko (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2025)
This study develops a Python-based configuration file management application to automate backup and recovery of network devices in the Universitas Kristen Duta Wacana laboratory, which uses Cisco and Mikrotik devices. The goal is to understand the impact of automation on the effectiveness of backup and recovery, support for remote configuration file management, reduction of recovery time, and its impact on operational sustainability. The Waterfall method is applied with the stages of analysis, design, implementation, testing, and evaluation, using network topology data, device information, and network protocols collected through observation, interviews, documentation, and literature studies. Testing includes scenarios of full and partial backup and recovery, error handling (credentials, lost files, unresponsive devices), and FTP server and database failure conditions on a network topology consisting of four identical blocks with Mikrotik routers and switches. The test results show that the application functions as expected, with all scenarios running smoothly without significant failures, including the ability to filter data according to parameters and detect credential errors. This system is concluded to have met the test objectives and is ready to be implemented.